ANALISIS PERKEMBANGAN PROGRAM PEMBERDAYAAN DESA (Studi Kasus UED-SP Candi Makmur di Kecamatan Pasir Penyu Kabupaten Indragiri Hulu) - Abid Rosyadi; Zaili Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Village empowerment program is program that aims to accelerate poverty reduction through community empowerment, provision of funding of rural enterprises, and strengthening the capacity of villages in rural development and independent participatory. The problem in this study is how the development of empowerment through Usaha Ekonomi Desa–Simpan Pinjam (UED-SP) Candi Makmur and constraints affecting the program in Candirejo village. The purpose of this study was to determine the extent of progress UED-SP candi makmur in encouraging the empowerment of the community Candirejo.The concept of the theory that researchers use is productive economic empowerment and empowerment of institutional capacity. The method used in this research is descriptive qualitative with data collection instrument includes interviews, observation and document data UED-SP candi makmur.The results of this study indicate that after the introduction of empowerment, community empowerment and institutional capacity increased. On refund loans are still experiencing arrears or congestion due to lack of a socialization about the clarity of program goals and background characteristics of the beneficiaries of diverse cultural culture.Keywords : Empowerment, Poverty, UED-SP